2016
DOI: 10.1111/bjd.14836
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors contributing to phenotypic divergence via quantitative image analyses of autosomal recessive woolly hair/hypotrichosis with homozygous c.736T>ALIPHmutation

Abstract: The difference in the frequency of underdeveloped hairs may be a major factor contributing to the clinical diversity of hair sparseness in LIPH c.736T>A homozygotes with ARWH/H. Hence, pharmacological modification to thicken existing fine hairs may provide a therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 25 publications
(57 reference statements)
0
25
0
Order By: Relevance
“…Recently, Kinoshita‐Ise et al . reported that the difference in the frequency of underdeveloped hairs might be a major factor contributing to the clinical diversity of hair sparseness in LIPH c.736T>A homozygotes with ARWH . We previously reported that patients with ARWH homozygous for c.742C>A showed a severe phenotype, and, in contrast, patients with mild hypotrichosis were seen among the patients with ARWH homozygous for c.736T>A.…”
Section: Summary Of the Patients With Autosomal Recessive Woolly Hairmentioning
confidence: 90%
“…Recently, Kinoshita‐Ise et al . reported that the difference in the frequency of underdeveloped hairs might be a major factor contributing to the clinical diversity of hair sparseness in LIPH c.736T>A homozygotes with ARWH . We previously reported that patients with ARWH homozygous for c.742C>A showed a severe phenotype, and, in contrast, patients with mild hypotrichosis were seen among the patients with ARWH homozygous for c.736T>A.…”
Section: Summary Of the Patients With Autosomal Recessive Woolly Hairmentioning
confidence: 90%
“…This suggests that other gene modifiers might play a role in phenotypic variability 1 . Histologically, there is no decrease in total hair count, but there is a remarkable miniaturization and an increased telogen/anagen hair ratio 5 . Spontaneous improvement has been described, and the effectiveness of topical minoxidil in the treatment of ARWH/H and other monogenic hair disorders has also been noted 5 .…”
Section: Figurementioning
confidence: 99%
“…Histologically, there is no decrease in total hair count, but there is a remarkable miniaturization and an increased telogen/anagen hair ratio 5 . Spontaneous improvement has been described, and the effectiveness of topical minoxidil in the treatment of ARWH/H and other monogenic hair disorders has also been noted 5 . However, topical minoxidil was not an effective treatment in these patients.…”
Section: Figurementioning
confidence: 99%
“…In an effort to provide such an assessment tool for geneticists and dermatologists, Kinoshita‐Ise et al . have examined eight patients with autosomal recessive woolly hair/hypotrichosis (ARWH/H) . ARWH/H is a nonsyndromic hair loss disorder, characterized by tightly curled hair, which can often be associated with hypotrichosis.…”
mentioning
confidence: 99%
“…While these reports show encouraging outcomes, a degree of caution should be exercised when interpreting these results, as sometimes hereditary hair conditions can improve spontaneously or following hormonal changes, such as pregnancy . Therefore, the use of minoxidil should be further examined in proper clinical studies, using suitable evaluation methods, such as the ones suggested in the study by Kinoshita‐Ise et al …”
mentioning
confidence: 99%